The development of polyester bead-based particulate subunit vaccine against Johne's disease : a thesis presented in partial fulfillment of the requirements of the degree of Master of Science in Microbiology, Massey University, Palmerston North, Institute of Fundamental Science - Sitthirit, Panan (Massey University, 2015)
Johne’s disease is the intestinal infection in ruminants caused by Mycobacterium avium subspecies paratuberculosis (MAP). The disease is economically important in the dairy industry as infection of the calves or mature cattle can result in death. Current vaccination as a part of disease control is not only partially protective against MAP but also interferes with current diagnostic test for bovine tuberculosis. Therefore, more effective and defined vaccines are needed. In this study, vaccine candidates were developed by bioengineering Escherichia coli to produce polyhydroxyalkanoate (PHA) beads displaying selected vaccine candidate antigens as fusion proteins. The selected antigens were the MAP 85 antigen complex (Ag85A and Ag85B), Superoxide dismutase (SOD) and a recombinant fusion protein 74F, however, only the antigenpresenting beads with truncated Ag85A, Ag85B and SOD were successfully produced and purified. The fusion protein comprising the respective antigens was identified and confirmed to be associated with PHA beads. The PHA beads were partially purified for future characterisations such as binding of antigen specific antibodies on PHA beads in vitro and immunological properties in animal models
Keywords: Escherichia coli; Biotechnology; Paratuberculosis; Johne's disease; Veterinary vaccines; Mycobacterium avium paratuberculosis